What Criminals' Tattoos Symbolize: Drawing on Darwin, Durkheim, and Lombroso. Issue 11 (2nd November 2017) - Jacques, Scott
ABSTRACT: Criminals' tattoos have many meanings. A limitation of prior research is that these meanings have not been organized into an elegant yet exhaustive typology that is theoretically informed. To address that gap, this article analyzes "Russian criminal tattoos" in light of classic conceptions of tattoos—namely those of Darwin, Durkheim, and Lombroso. The benefits of the analysis include (1) an expanded conception of what tattoos symbolize from Darwinian and Durkheimian perspectives and (2) the formation of a simple but comprehensive typology of what criminals' tattoos represent. The article concludes by considering implications for future research.